Analysis of Coolant Purification Strategies for Tritium Control in DEMO Water Primary Coolant - Vincenzo Narcisi; Andrea Quartararo; Ivo Moscato; Alessia Santucci (Energies, 2023)
A major objective of the European fusion program is the design of the DEMOnstration power plant named DEMO. Up to now, most fusion experiments have been dedicated to a plasma physics investigation while, in DEMO-oriented activities, large attention is devoted also to other systems necessary to produce tritium and to convert the fusion power to electricity. The blanket region, responsible for tritium breeding, is characterized by high tritium concentrations, high temperature, and large heat transfer metallic surfaces in which tritium can permeate. Therefore, the problem of tritium permeation and the resulting tritium content in the primary coolant are of great relevance for DEMO. For the pre-conceptual design of the Water-Cooled Lead–Lithium variant, the tritium permeation rate from blanket into coolant was assessed and possible mitigation strategies were suggested. Starting from a review of the CANDU tritium experience, a preliminary assessment of the maximum tritium concentration target in the DEMO primary coolant was performed and different strategies (off-line, on-line, and hybrid) for the water coolant purification system coupled with the DEMO operating scenario were analyzed. The intent is to identify suitable solutions to reduce the tritium concentration inside the water coolant, having in mind the complexity of a water detritiation process.